2169. Map the Gap: A Novel Approach Using Big Data to Determine the State of the Infectious Diseases Workforce and Fecal Transplant Centers with Regards to Clostridium Difficile Infection. (26th November 2018) - Shah, Aditya; Stone, Eric; O'horo, John C
Abstract: Background: Clostridium difficile infection (CDI) is the most common healthcare-associated infection in the United States, accounting for almost half a million infections in the United States in 2011, and 29, 000 attributable deaths. Fecal transplant centers are emerging all over the country, as options for therapy in severe and recurrent CDI. Currently, there is little data regarding how well matched the supply of infectious disease and fecal transplant providers are to the CDI demand. Methods: Deidentified data about the number of board certified Infectious Disease physicians by zip code was obtained from the Doximity physician database, a resource which is up to date and refreshed monthly. The location of current Infectious Disease fellowships was obtained from the National Resident Matching Program public data. These were mapped using Google fusion tables and compared with CDI prevalence rates from data gathered via HCUPNET for National Inpatient Sample data. These were in turn compared with the spread of FDA approved centers to perform fecal transplants over the country. Results: A total of 7, 129 Infectious Disease physicians and 147 fellowship programs were identified. Our results indicate that Infectious Disease specialists and fellowship programs tend to be more concentrated in the Northeast and metropolitan areas in the Western regions of the United States, with parallel similar patterns noted in other specialties. CDI prevalence rates were highest in Florida, Texas and California, followed by New York and Illinois. This correlated well with the spread of fecal transplant centers, however, not with the spread of the infectious disease workforce. Conclusion: The use of this novel social network mapping methodology approach to assess the Infectious Disease physician workforce has the potential of providing real-time data regarding their spread. These data may highlight a discrepancy between supply and demand which may need targeted rebalancing interventions that may include additional fellowship spots in"underserved' areas as well as financial and practice incentives. Interestingly, there appears to be a good correlation between spread of fecal transplant centers with the prevalence of Clostridium difficile cases, perhaps providing an example of an area where incentives are aligned to meet patient need. Disclosures: All authors: No reported disclosures.